Efficiency of Indian Banks – private versus public sector banks: A two-stage analysis - Biswajit Patra; Purna Chandra Padhan; Puja Padhi (Cogent Economics & Finance, 2023)
This paper estimates and compares various efficiencies, namely, business, profit, and Z-Score efficiencies for private and publicly owned Indian banks. It uses the data envelopment analysis (DEA) following variable returns to scale, under input and output orientation, for measuring efficiency. Further, the Tobit regression model is used in the second stage to check the significant determinants from a list of bank-specific factors for various efficiencies. The study finds that the average efficiency scores of public sector banks (PSBs) are higher than private banks. The Z-score indicates that both PSBs and private banks are facing stability risks. Tobit regression model results confirm that return on assets and capital levels are significantly related to all types of efficiencies for private banks. On the other hand, the efficiency of PSBs is mainly affected by the level of non-performing assets, market share, size of the bank, return on assets, and capital level. It is inferred that the prompt corrective action (PCA) framework of RBI (2014) and the merger and consolidation of PSBs by the government (2019) favorably impacted the efficiencies of PSBs. Additionally, it identifies the stability risk of Indian banks and suggests banks should build up adequate capital for stressful situations.
Keywords: C67; G210; 330; banks; DEA; efficiency; Tobit model; two-stage analysis; Z-score